ENGLISH LISTENING BLENDED LEARNING: THE IMPLEMENTATION OF BLENDED LEARNING IN TEACHING LISTENING TO UNIVERSITY STUDENTS - Aji, Mahendra Puji Permana (Kajian Linguistik dan Sastra, 2017)
As one of the English skills, listening needs more than one instance in hearing because it is not only hearing but also understanding and interpreting the meaning of the conversation. Therefore, to make the students interested and easy to understand in listening, the lecturer applied blended learning. The primary focus of this research is to observe the implementation of blended learning in teaching listening. This is a qualitative research of which the subject is the students in one class. There are 28 students, 9 males and 19 females. The data were collected by interviewing the listening lecturer, observing the activities in the classroom and giving the questionnaire to the students. The result of the research showed that the implementation of blended learning in teaching listening at university was able to improve the studentsâ listening skill. In summary, this study demonstrated that the use of blended learning in teaching listening offered ways for lecturers to be more effective in the teaching and learning process and brought positive outcomes for the students.Â Keywords: Blended learning, listening, teachingÂ